Ancient wisdom : an introduction to sayings collections - Wilson, Walter T. (Grand Rapids, Michigan: William B. Eerdmans publishing company, 2022)
"An introduction to all the major extant collections of wisdom sayings from antiquity"--
ʼAbot -- Ahiqar -- Amenemope -- Anii -- Ankhsheshonqy -- Ben Sira -- Cato -- Counsels of wisdom -- Democritus -- Epictetus -- Papyrus Insinger -- Isocrates -- Menander -- Merikare -- Pseudo-Phocylides -- Porphyry -- Proverbs -- Ptahhotep -- Publilius -- Pythagorean collections -- The seven sages -- Sextus -- Shuruppak -- Silvanus -- Sumerian proverb collections -- Syriac Menander -- The gospel of Thomas.
Includes bibliographical references and indexes.
Keywords: Proverbs -- History and criticism; Maxims -- History and criticism; Wisdom -- Quotations, maxims, etc; Literature, Ancient -- History and criticism; Wisdom literature -- Criticism, interpretation, etc; RELIGION / Biblical Studies / History & Culture; RELIGION / Biblical Studies / General